2019
DOI: 10.7717/peerj.8077
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling analysis reveals key genes of different coat color in sheep skin

Abstract: BackgroundTo investigate the molecular mechanisms determining the coat color of native breed sheep in Xinjiang.MethodsBashibai sheep, Yemule white sheep and Tulufan black sheep were selected. Illumina HiSeq X Ten sequencing technology was used to detect the genes responsible for the white, light brown, black and cyan gray coat colors in sheep. Sequence analysis and functional gene annotation analysis were performed to analyze the results. The signal pathways and differentially expressed genes related to sheep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The neuroactive ligand-receptor pathway has the most DEGs ( 15 ) in the hypothalamus, followed by the Notch signaling pathway, ovarian steroidogenesis, and the calcium signaling pathway, which were related to reproduction. In the pituitary, the cytokine-cytokine receptor interaction pathway had the most DEGs ( 12 ), whereas the P53 signaling pathway, cell adhesion molecules (CAMs), the NF-kappa B signaling system, and oocyte meiosis were involved in reproduction regulation. In addition, the largest number of DEGs in the ovary was in the human papillomavirus infection pathway ( 16 ), and the reproduction-related pathways included the “Hippo” signaling pathway, CAMs, arachidonic acid metabolism, and AMPK signaling pathway.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The neuroactive ligand-receptor pathway has the most DEGs ( 15 ) in the hypothalamus, followed by the Notch signaling pathway, ovarian steroidogenesis, and the calcium signaling pathway, which were related to reproduction. In the pituitary, the cytokine-cytokine receptor interaction pathway had the most DEGs ( 12 ), whereas the P53 signaling pathway, cell adhesion molecules (CAMs), the NF-kappa B signaling system, and oocyte meiosis were involved in reproduction regulation. In addition, the largest number of DEGs in the ovary was in the human papillomavirus infection pathway ( 16 ), and the reproduction-related pathways included the “Hippo” signaling pathway, CAMs, arachidonic acid metabolism, and AMPK signaling pathway.…”
Section: Resultsmentioning
confidence: 99%
“…In the past, studies have found a number of important genes and pathways regulating animal reproduction by high-throughput sequencing in the HPO axis of female animals ( 8 , 9 ). In sheep, many studies have focused on transcriptome sequencing analysis of muscle tissue ( 10 ), adipose tissue ( 11 ) or skin tissue ( 12 ) and have identified a number of candidate markers. Meanwhile, RNA-Seq was also been used to investigating reproductive regulation mechanism of animals.…”
Section: Introductionmentioning
confidence: 99%
“…Variations in the TYR gene cause melanin deficiency in human eyes, skin, and hair, resulting in albinism [ 38 , 39 ]. The mRNA expression of the TYR gene was significantly different in black and white sheep [ 40 ], dark-gray and light-gray goats [ 41 ], black and white feather ducks [ 42 ], as well as black and white feather chickens [ 43 ]. Additionally, there were significant differences in dark-gray and light-gray goat black fibers and different black-bone chicken muscles [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Table S10. Additional genetic studies on sheep coat color variation [310][311][312][313][314][315][316][317][318][319][320][321][322][323][324][325][326][327]. Table S11.…”
Section: Supplementary Informationmentioning
confidence: 99%